2020
DOI: 10.17765/2176-9168.2020v13n1p397-409
|View full text |Cite
|
Sign up to set email alerts
|

Análise exploratória dos impactos das mudanças climáticas na produção vegetal no Brasil

Abstract: Um dos problemas na agropecuária mundial é produzir sob efeito das mudanças climáticas, e esta atividade propicia impacto ao meio ambiente, principalmente na geração de gases do efeito estufa. Portanto o objetivo do presente trabalho será realizar uma análise exploratória sobre a situação e adaptação da produção vegetal em meio às mudanças climáticas, o reflexo de sua degradação na saúde humana, identificando as opções de mitigação das emissões causadas por atividades agrícolas e as oportunidades associadas a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Rainfed agriculture in arid and semi-arid regions is difficult to establish because of the spatiotemporal variations in rainfall in these areas (Félix et al, 2020;Mbava et al, 2020). Therefore, irrigation plays an important role in reducing losses and maximizing crop productivity by improving the spatiotemporal distribution of water in arid and semi-arid regions (Ferraz et al, 2019;Kankarla et al, 2019;Morais et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfed agriculture in arid and semi-arid regions is difficult to establish because of the spatiotemporal variations in rainfall in these areas (Félix et al, 2020;Mbava et al, 2020). Therefore, irrigation plays an important role in reducing losses and maximizing crop productivity by improving the spatiotemporal distribution of water in arid and semi-arid regions (Ferraz et al, 2019;Kankarla et al, 2019;Morais et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Increases of 1.7 to 4.8 °C in the average air temperature, changes in rainfall patterns, and the occurrence of extreme events are some of the climate changes predicted by the Intergovernmental Panel on Climate Change (IPCC) (IPCC, 2013). These scenarios will directly influence the availability and use of natural resources, including crop cultivation (Magrin et al, 2014;Félix et al, 2020). Long droughts and high temperatures characterize the climate in the Brazilian semiarid region.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies have shown the effects of global warming on agriculture (Heinemann et al 2009, Félix et al 2020. However, the impacts of adaptation practices have not yet been fully addressed, although efforts have been made to overcome them (Brasil 2021b).…”
Section: Introductionmentioning
confidence: 99%